Infective endocarditis and pregnancy - S. O. Siromakha; A. O. Rusnak; O. F. Luchinets; A.O. Ogorodnyk; T. A. Malysheva; V. V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2019)
Infective endocarditis in pregnant women is a threatening disease that leads to significant maternal and perinatal losses. Methods for caring for such patients have not yet been standardized, and literature sources provide single descriptions of case reports.Objectives. To reduce maternal and perinatal mortality and disability, as well as to provide optimal management and delivery strategy for pregnant women with infective endocarditis.Materials and methods.This paper presents the experience of treating three cases of IE in pregnant women (n-2) and parturient (n-1) by specialists of a national multidisciplinary team. In all three cases, cardiology, cardiac surgery and perinatal tactics were personalized in accordance with the recommendations of the European Society of Cardiologists and the experience of the team members. Parturient with acute IE and septic clot of right ventricle underwent urgent cardiac surgery. Another pregnant was provided with conservative support by a multidisciplinary team due to the absence of indications for immediate surgery (she underwent aortic valve replacement and mitral valve repair in 11 days after in-term labour). The third one underwent cardiac surgery (mitral valve repair) with fetus in utero at 21 weeks of pregnancy after 11 weeks of de-escalation therapy by antibiotics.Results. In all cases, the immediate maternal and perinatal results were good. Follow-up for two cases we could observe (33 and 18 months after surgery) are good.Conclusions. Treatment tactic for pregnant women with acute IE that require heart surgery is always a compromise between the treatment and rehabilitation of a deep-preterm baby and the intra-operative risks to the fetus. Risk of intervention for mother and fetus can be minimized by a highly professional multidisciplinary team with wide experience in open-heart surgery, competent preparation of women for surgical treatment, conducting intraoperative fetal monitoring, as well as using special parameters of artificial circulation and anesthesia. Primary and secondary prevention of infectious complications in pregnant women at risk of IE is a powerful tool to reduce maternal, perinatal mortality and disability.